Determinants of intention to return to donate blood among first‐time blood donors in Ghana. Issue 3 (7th November 2020) - Asamoah‐Akuoko, Lucy; Ullum, Henrik; Appiah, Bernard; Hassall, Oliver W; Ndanu, Thomas; Adongo, Philip; Bates, Imelda
Abstract : Objective: This study seeks to identify factors that are predictive of intention to return to donate blood among first‐time blood donors. Methods: A cross‐sectional survey of 505 first‐time blood donors, selected from blood donation sessions across three regions in Ghana. Data were obtained on their intention to donate blood in the next four months, factors that would influence this decision. Logistic regression models were used to test factors that were predictive of intention to return. Results: First‐time donors were young with 87·4% below 35 years of age, male (72·5%), single (73·3%), Christian (93·7%), employed (58·8%), with at least a basic education (98%). Factors that positively predicted intention to return included: motivational incentives (OR = 1·67, 95%CI: 1·01–2·78; P  = 0·045); ease of access to the donation site (OR = 2·65, 95%CI: 1·48–4·73; P  = 0·001); SMS and email reminders (OR = 2·84, 95%CI: 1·60–5·06; P  < 0·001); and television, radio or newspaper advertisements (OR = 2·97, 95%CI: 1·66–5·31; P  < 0·001). Factors that negatively predicted intention included preferential access to transfusions (i.e. 'blood credits') (OR = 0·43, 95%CI: 0·23–0·83; P  = 0·012); getting to know test results (OR = 0·40, 95%CI: 0·20–0·80; P  = 0·010); and not knowing and/or trusting what happens to the blood after donating (OR = 0·50, 95%CI: 0·28–0·88; P  = 0·016). Conclusion: Motivational incentives, convenient access to donation sessions, reminders and mass media advertisements appear to positively influence intention to return to donate. Conversely not knowing what happens to the blood after donation negatively influenced intention to return. Interventions to promote repeat blood donation should consider the identified factors.